The Role of Employee Training, Job Satisfaction, and Career Advancement in Enhancing Performance in Higher Education Institutions - Suriadi, Suriadi; Jasiyah, Rabiyatul; Farawowan, Fauziah F; Salma, Nur (PT. BATARI EDU CALYA, 2024)
This study examines the impact of employee training, job satisfaction, and career advancement on employee performance in higher education institutions (HEIs). Using a quantitative research design, data were collected from 300 employees across various HEIs. The findings indicate that all three factors significantly enhance employee performance, with job satisfaction emerging as the most influential predictor. Effective training programs positively correlate with increased job satisfaction, while perceived opportunities for career advancement further motivate employees to perform at their best. The results suggest that HEIs should prioritize comprehensive employee development strategies that integrate training, satisfaction, and career growth opportunities to foster a supportive work environment. This research contributes to the understanding of how these factors interrelate to enhance employee performance and provides actionable recommendations for HEI administrators and policymakers